Covid-19 and its repercussion on the nutritional Status and gestational Anemia from sociodemographic-obstetric factors - Boza Valverde, Luis (2021)
Introduction: Currently, the impact of COVID-19 on sociodemographic and obstetric factors, linked to nutritional status and anemia in pregnant women, represents a significant change in management and healthcare paradigms. Objectives: To consider a multiple logistic regression model and multiple comparisons (Mann-Whitney U test) based on sociodemographic-obstetric factors, nutritional status and anemia in pregnant women before and during Covid-19. Methods: In this study, 113 medical records of pregnant women attended between November 2019 and April 2020 at a Hospital II-1 in Trujillo, Peru were analyzed. Multiple logistic regression model showed a good fit and allowed to correctly classify most of pregnant women. Results: The covariates; employment situation, obstetric history, nutritional condition and anemia were significant. Differences were observed between sociodemographic factors such as employment status, obstetric factors such as obstetric history, and factors related to nutritional status and clinical symptoms of anemia. Conclusions: The impact of COVID-19 reflected in the relationships between sociodemographic and obstetric factors with nutritional status and the anemia diagnosed in pregnant women treated in a Hospital II-1 in Trujillo, Peru, was evidenced.